PENGARUH KESADARAN WAJIB PAJAK, KEGIATAN SOSIALISASI PERPAJAKAN, PEMERIKSAAN PAJAK DAN JUMLAH WAJIB PAJAK YANG TERDAFTAR TERHADAP PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI DI KPP PRATAMA PEKANBARU TAMPAN - Wielda Permata Sari; Raja Adri Satriawan; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aimed to find out whether taxpayers’ awareness, tax socialization, and tax inspection have a significant influence, The number of registered taxpayers to income tax receivable in Pekanbaru Tampan Tax Authority. Taxpayers’ awareness is measured with the percentage of Income Tax Article 25 monthly tax return that reported on time. Tax socialization is measured by the number of tax socialization events that held by Pekanbaru Tampan Tax Office with the focus on personal taxpayer. Tax inspection is being observed from the number of income tax article 25 tax collection letter that issued for personal taxpayer. The number of registered taxpayers is being observed from The number of registered taxpayers every month. Income tax receivable is being observed from the number of income tax article 25 installment payment revenue that paid by personal taxpayer at Pekanbaru Tampan Tax Office. The data type that being used in this research were quantitative data by using monthly secondary data from fiscal year 2011 until 2014. The applied statistic test was multiple linier regressions. This research proved that taxpayers’ awareness have a significant influence to income tax receivable, tax socialization have a significant influence to income tax receivable, tax inspection simultaneously had no influence and The number of registered taxpayers had no influence to income tax receivable in Pekanbaru Tampan.Keywords: Taxpayers’ Awareness, Tax Socialization, Tax Inspection, Income Tax Receivable, and Income Tax Article 25